CEO : - Kurtzig, Sandra L. (Harvard Business School Press, 1994)
This edition features a new introduction in which Kurtzig draws on her own experiences to provide insight into the sources of entrepreneurial success - leadership, vision, strategic thinking and the ability to make decisions and take risks.